Response Characteristics of Nitrifying Bacteria and Archaea Community Involved in Nitrogen Removal and Bioelectricity Generation in Integrated Tidal Flow Constructed Wetland-Microbial Fuel Cell - Wang, Longmian; Pang, Qingqing; Peng, Fuquan; Zhang, Aiguo; Zhou, Ying; Lian, Jianjun; Zhang, Yimin; Yang, Fei; Zhu, Yueming; Ding, Chengcheng; Zhu, Xiang; Li, Yiping; et al. (Frontiers in Microbiology, 2020)
This study explores nitrogen removal performance, bioelectricity generation, and the response of microbial community in two novel tidal flow constructed wetland-microbial fuel cells (TFCW-MFCs) when treating synthetic wastewater under two different chemical oxygen demand/total nitrogen (COD/TN, or simplified as C/N) ratios (10:1 and 5:1). The results showed that they achieved high and stable COD, NH4+-N, and TN removal efficiencies. Besides, TN removal rate of TFCW-MFC was increased by 5–10% compared with that of traditional CW-MFC. Molecular biological analysis revealed that during the stabilization period, a low C/N ratio remarkably promoted diversities of ammonia-oxidizing archaea (AOA) and ammonia-oxidizing bacteria (AOB) in the cathode layer, whereas a high one enhanced the richness of nitrite-oxidizing bacteria (NOB) in each medium; the dominant genera in AOA, AOB, and NOB were Candidatus Nitrosotenuis, Nitrosomonas, and Nitrobacter. Moreover, a high C/N ratio facilitated the growth of Nitrosomonas, while it inhibited the growth of Candidatus Nitrosotenuis. The distribution of microbial community structures in NOB was separated by space rather than time or C/N ratio, except for Nitrobacter. This is caused by the differences of pH, dissolved oxygen (DO), and nitrogen concentration. The response of microbial community characteristics to nitrogen transformations and bioelectricity generation demonstrated that TN concentration is significantly negatively correlated with AOA-shannon, AOA-chao, 16S rRNA V4-V5-shannon, and 16S rRNA V4-V5-chao, particularly due to the crucial functions of Nitrosopumilus, Planctomyces, and Aquicella. Additionally, voltage output was primarily influenced by microorganisms in the genera of Nitrosopumilus, Nitrosospira, Altererythrobacter, Gemmata, and Aquicella. This study not only presents an applicable tool to treat high nitrogen-containing wastewater, but also provides a theoretical basis for the use of TFCW-MFC and the regulation of microbial community in nitrogen removal and electricity production.